EXPOsure: Milan, May 1st- October 31st 2015 - Zuccotti, Gian Vincenzo (Ital J Pediatr, 2015)
The city of Milan is experiencing the great event of EXPO 2015 and heavy construction has been ongoing since 2012 over an area of more than 1 million meters squared in the north-west suburban area of the city. We compared the number of hospital admissions for upper and lower respiratory tract infections (URTI and LRTI) and acute asthma, in infants and children aged between 0 and 13 years from 2011 to 2014 in two Pediatric Departments, one near and one far from the EXPO construction area. Hospital admission frequencies resulted to be similar in the two Pediatric Departments.